2019
DOI: 10.2136/sssaj2019.04.0123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation Water pH on Saturated Hydraulic Conductivity and Electrokinetic Properties of Acidic, Neutral, and Alkaline Soils

Abstract: The demand for the use of marginal‐quality water as an irrigation resource is increasing in arid and semiarid region lands due to the freshwater shortage. Marginal waters usually have high salinity and high alkalinity and may contain high proportions of ions such as sodium. This study investigated the impact of irrigation water pH on saturated hydraulic conductivity (Ks), cation exchange capacity, net particle charge, and dispersivity of soils. Nine soils with differing pH, alkalinity, clay content, and minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Most existing models for the dynamics of salinity and sodicity, by contrast, are not capable of considering the effect of soil type on changes to hydraulic conductivity. While the advantages of a soil‐specific approach have been demonstrated, the incorporation of soil‐specific considerations into existing models for the dynamics of salinity and sodicity has been hampered, possibly due to difficulties in modifying the code of these existing models (Ali et al, 2019; van de Craats et al, 2020). As an open‐source program coded in Python, SOTE is easily amenable to user modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Most existing models for the dynamics of salinity and sodicity, by contrast, are not capable of considering the effect of soil type on changes to hydraulic conductivity. While the advantages of a soil‐specific approach have been demonstrated, the incorporation of soil‐specific considerations into existing models for the dynamics of salinity and sodicity has been hampered, possibly due to difficulties in modifying the code of these existing models (Ali et al, 2019; van de Craats et al, 2020). As an open‐source program coded in Python, SOTE is easily amenable to user modifications.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that the initial soil pH is not important in predicting the hydraulic conductivity decline. However, we caution that this assumption is on the basis of the study of Ali et al (2019), who demonstrated that the initial soil pH and the clay content were both important in controlling the extent of the hydraulic conductivity reduction. The same nine soils were used in this work.…”
Section: Soil Initial Ph and Hydraulic Conductivity Reductionmentioning
confidence: 96%
“…3). From these data, a generalized r 2 function was also formed using the same approach as Šimůnek and Suarez (1997), based on the results of r K s for the soils used in the study of Ali et al (2019) and presented in (Fig. 1 and 2).…”
Section: Modification Of the Hydraulic Reduction Scaling Factor For Phmentioning
confidence: 99%
“…This might take place because both the clay and organic matter contents in soils probably formed layers of low filtration rates (Patle et al, 2019). Moreover, clay particles reserve Na ions in soil; which consequently increased clay dispersion (Ali et al, 2019), while decreased soil hydraulic conductivity (Arienzo et al, 2012).This is an important aspect for water and salts transportation (Klopp and Daigh, 2019). Thus, there is no wonder to find out that the total concentrations of trace elements significantly and negatively correlated with soil ESP (Table 2).…”
Section: Ab-dtpa Extractable (Available) Contents Of Trace Elements Imentioning
confidence: 99%